2004
DOI: 10.1111/j.1440-1746.2003.02891.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal tumor of the pancreas with expression of c‐kit protein: Report of a case

Abstract: We report on a case of a stromal tumor, similar to a gastrointestinal stromal tumor, originating from the pancreas. The patient was a 54-year-old woman, who was seen at the Kofu Municipal Hospital because of an abdominal tumor. On abdominal computed tomography and splenic arteriography, the tumor was detected in the pancreatic tail. The patient underwent distal pancreatectomy with splenectomy. Macroscopically, the cut surface of the tumor showed almost completely surrounded by the normal pancreatic tissue. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 7 publications
0
34
2
1
Order By: Relevance
“…In the differential diagnosis, a recurrent/metastatic GIST, which can also form a mass in the vicinity of the pancreas, was mentioned. However, there was no history of GIST in the two cases and in contrast to the reported stromal tumor of the pancreas, 24 the disorderly endocrine and exocrine pancreatic tissue embedded in the stroma in our cases does not readily fit the diagnosis of GIST. The expression of c-kit is required for the diagnosis GIST, but c-kit expression is not specific to this tumor entity.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In the differential diagnosis, a recurrent/metastatic GIST, which can also form a mass in the vicinity of the pancreas, was mentioned. However, there was no history of GIST in the two cases and in contrast to the reported stromal tumor of the pancreas, 24 the disorderly endocrine and exocrine pancreatic tissue embedded in the stroma in our cases does not readily fit the diagnosis of GIST. The expression of c-kit is required for the diagnosis GIST, but c-kit expression is not specific to this tumor entity.…”
Section: Resultscontrasting
confidence: 99%
“…The spectrum of pancreatic mesenchymal neoplasms was recently expanded by the description of an extragastrointestinal stromal tumor in the pancreas. 24 The tumor consisted of spindle-shaped cells that were immunoreactive for vimentin, CD34 and c-kit. In contrast to our cases it lacked any pancreatic exocrine or endocrine component.…”
Section: Resultsmentioning
confidence: 99%
“…Last year, Yamaura et al [61] reported a case of a pancreatic stromal tumor, similar to GIST, since the spindle-shaped tumoral cells were immunoreactive for c-kit, CD34 and vimentin. Beyond the origin from primitive mesenchymal cells suggested by the authors, we consider that such tumor may originate from a subset of pICC that we described here.…”
Section: Discussionmentioning
confidence: 99%
“…Spindle cell tumors similar to GIST have been reported in the extra-gastrointestinal sites such as omentum, mesentery, urinary bladder, gallbladder, retroperitoneum, and pancreas [103][104][105][106][107][108][109][110] and their incidence is frequent enough to be separately categorized as extra-gastrointestinal stromal tumors (eGIST). They seem to be indistinguishable from GIST in their cytomorphology, c-Kit expression and genetic changes.…”
Section: Extra-gastrointestinal Stromal Tumors (Egist)mentioning
confidence: 99%